Treatments and supportive therapies for oral manifestations of chronic graft-versus-host disease - Rafaella Gabriel Maiolino; Amanda Lury Yamashita; Lilian Cristina Vessoni Iwaki; Liogi Iwaki Filho; Wilton Mitsunari Takeshita; Mariliani Chicarelli (Acta Scientiarum. Health Sciences, 2016)
The aim of this study was to conduct a systematic review of treatments and therapies for oral manifestations of chronic graft-versus-host disease, aiming at improving patients’ quality of life and mainly the reduction of mortality caused by graft-versus-host disease. A systematic review was carried out by two evaluators, a Dentistry professor and an undergraduate student. A selection of open-access full-text online articles, carried out on PubMed, GoPubmed, NLM Gateway, LILACS, BIREME, SciELO, IBECS, and Web of Science. The survey was completed in July 2012. Of the 1147 studies found, 52 fit the selection criteria. Patients (n = 2130) received different treatment regimens, either systemic or topical. Drugs for systemic therapy were divided into those with action on the inhibition of proliferation and/or release of T and B cells, with action on inflammatory disorders, and of immunomodulatory effect. Topical drugs were divided into their pattern of mucosal absorption and their ability to act on tissue growth factors. The analysis of articles concluded that the most used systemic drugs were Methylprednisolone and corticosteroids, and Tacrolimus and topical Cyclosporine for topical and local therapy.